Plucked Hair as a Substrate for Indirect Immunofluorescence in Cases of Pemphigus Vulgaris - Kumaresan, Muthuvel (Int J Trichology, 2020)
INTRODUCTION: Indirect immunofluorescence (IIF) is used to determine the circulating autoantibodies in cases of Pemphigus. For IIF in Pemphigus several substrates had been used. This study was done to determine whether plucked hair can be utilized as a substrate for IIF in cases of Pemphigus. Aim & Objectives: To determine the efficacy of utilizing the plucked hair as a substrate for indirect immunofluorescence among patients with Pemphigus vulgaris. METHODOLOGY: Thirty two consecutive patients with active and fresh diagnosed cases of pemphigus vulgaris (PV) who did not undergo any treatment and those patients who had positive DIF findings of characteristic fish net or chicken wire pattern of intercellular IgG deposits in the epidermis of perilesional skin were included in the study. A total of 32 control subjects without any auto immune disorders were selected and the blood samples were taken from these patients for IIF analysis. Anagen hair were collected from the healthy volunteers without pemphigus in the same way as for trichogram. Telogen hair were obtained by combing the hair and collecting the loose strands of hair on the comb and further confirmed under microscope. Three hairs each of anagen and telogen stage were collected from each subject to be utilized as a substrate for IIF. RESULTS: Out of 32 samples 20 samples showed positive results for Ig G alone and 5 samples showed positivity for Ig G and C3. One sample showed positivity for C3alone. All these 26 samples were considered to have positive IIF test based on the intercellular pattern of deposit. Positive IIF results were observed in anagen hair samples and were negative in all the telogen hair samples. Six anagen hair samples did not show any positive findings in IIF for the study group. All the 32 control samples showed negative reports in IIF. CONCLUSION: In conclusion, IIF microscopy on plucked hair as a substrate is a more sensitive immunoassay for the detection of circulating intercellular autoantibodies in PV and the lower negative predictive value of this substrate is a limitation. Further large scale studies might provide better information regarding the practical utility.